Early childhood development practitioner’s experience of the occupation of nurturing with children from birth to five years: a descriptive qualitative study - Stemmert, Barbara (Department of Health and Rehabilitation Sciences, 2020)
Introduction The purpose of this qualitative descriptive study was to describe the meaning of what the occupation of nurturing was for Early Childhood Development (ECD) practitioners practicing in Khayelitsha educares. This information gave rise to a shared understanding of what the occupation of nurturing was for ECD practitioners. An occupation not explored on the national or international platforms though greatly needed in supporting a thriving learning environment for young children. The Aim The aim was to describe the experiences of ECD practitioner’s occupation of nurturing within educares in a low socio- economic environment of Khayelitsha. The Objectives To describe the ECD practitioners experience of participating in the four-day psychosocial Healing Arts training workshop facilitated by Bambelela. To explore how the ECD practitioner’s self-awareness informed their understanding of their occupation of nurturing in providing a nurturing learning environment. To describe what the enablers and barriers were as experienced by ECD practitioners in fulfilling their occupation as nurturer. To describe practitioner’s understanding of how their behaviour influenced the learning environment in how children learn. The Methodology Application of the qualitative approach utilized the descriptive tradition of inquiry which captured the nurturing experiences of the participants. The application of purposeful sampling in the selection of participants guided by the inclusion and exclusion criteria ensured a standardized baseline of skills and training. Data collected used semi structured interviews, document reviews, researcher notes and member checking for data verification. The data analyses process was guided by the application of the five stages as described by 4 Pope, Ziebland and May namely familiarization, thematic framework development, indexing, charting and mapping. The data analyses stages were guided through familiarization of the saturated data collected, which led to the identification of a thematic framework. This framework informed a structured process, which linked participant’s responses to the study’s objectives. The indexing comprised of the development of codes from the data, after further sorting and clustering the categories evolved. The charting process provided more information as the data was sorted into categories. This process further collapsed the categories, which informed the development of three themes. The mapping of categories per theme was undertaken, which informed the various facets interacting and diverging in the occupation of nurturing. Guba’s model guided the scientific rigour of the study by focusing on credibility, transferability, dependability and confirmability. Findings Three themes emerged The Journey, The Awakening and The Game Changers. The findings showed the value in sharing life experiences through interaction with peers, which led to healing. Practitioners shared their positive and negative attitudes towards child handling as well as the power of knowledge and self-regulation. Exploration of the technical skills needed for child stimulation and management, characteristics of a practitioner, and environmental enablers and barriers. Conclusion The findings elucidated that practitioners became aware of the attributes and skills needed to provide children with a positive, caring and stimulating foundation within an educare. They achieved this through guided group facilitation in the psychosocial training workshop, which in turn ignited a healing process. The holistic approach to the practitioner training created the awareness and motivation for them to explore their occupation of nurturing. They articulated the critical enablers and barriers to their role as practitioner in fulfilling this occupation.